THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL INCLUSION AND FINANCIAL TECHNOLOGY ON THE FINANCIAL PERFORMANCE OF UMKM IN PADANGSIDIMPUAN CITY - Pulungan, Ismail (Journal of Islamic Financial Technology, 2024)
Financial performance problems in Micro, Small and Medium Enterprises (MSMEs) are generally related to the lack of management capabilities in managing working capital, which causes difficulties in measuring financial performance. Several factors that affect the financial performance of MSMEs include the quality of financial reports, financial literacy, financial inclusion and financial technology . The discussion of this study is related to the field of MSME financial performance science in relation to the theory that financial literacy affects the financial performance of MSMEs, financial inclusion affects the financial performance of MSMEs as well as Financial technology affects the financial performance of MSMEs. This research is a quantitative study. The data collection instrument uses a questionnaire with a sample size of 100 MSMEs. The analysis tools used are validity tests, reliability tests, classical assumption test analysis, multiple linear regression and hypothesis tests. The results of the study show that financial literacy (X1) affects the financial performance of MSMEs (Y). The financial inclusion variable (X2) does not affect the financial performance of MSMEs (Y). The financial technology variable (X3) affects the financial performance of MSMEs (Y). Meanwhile, simultaneously, the variables of financial literacy (X1), financial inclusion (X2) and financial technology (X3) have an effect on the financial performance of MSMEs (Y).